Question Number 104777 by Anindita last updated on 23/Jul/20

Answered by Aziztisffola last updated on 23/Jul/20

3.5+4.5=8  +         +  9.5−3.5=6  13        8

Answered by 1549442205PVT last updated on 24/Jul/20

We have the following system of four  equations: { ((x+y=8(1))),((z−t=6(2))),((x+z=13(3))),((y+t=8(4))) :}  From (1)(4)we get x=t=8−y(5)  subtract two eqs.(2)and(3)we get  x+t=7⇒2x=2t=7(by (5))⇒x=t=3.5  (4)⇒y=8−3.5=4.5,(2)⇒z=6+t=9.5  Thus,we get (x,y,z,t)=(3.5;4.5;9.5;3.5)   determinant (((3.5),+,(4.5),=,8),(+,,+,,),((9.5),−,(3.5),=,6),(=,,=,,),((13),,8,,))

Answered by Rasheed.Sindhi last updated on 24/Jul/20

 determinant (( [((           x)),((2x+6=13)),(( x=3 1/2_(−)         )) ],→_+ , [((     8−x)),((8−3 1/2  )),((    4 1/2)) ],8),((            ↑+),,(          ↓+),),( [((         x+6)),((     3 1/2+6    )),((=9 1/2)) ],←_− , [((8−(8−x))),((         x)),((    3 1/2)) ],6),((−−−−−−−),−,(−−−−−−),−),((            13),,(           8),))